2019
DOI: 10.1055/s-0039-3400840
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Morphometry of North Indian Acetabula—Forensic and Orthopedic Consideration

Abstract: Background Acetabulum is a cup-shaped cavity of the hipbone. It constitutes the acetabular part of the hip joint. Its shape and position related to the head of the femur are crucial for the biomechanics of this joint. The knowledge of various acetabular dimensions is essential to diagnose various diseases of hip joint, to monitor patient recovery, to determine stability of the hip joint, to assess acetabular dysplasia, and also to create patient-specific acetabular implants in case of hip arthroplasty. Various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…In addition, a very strong positive statistically significant correlation was obtained between LH and IH (r: 0.853, p<0.001) and ADA and VDA (r: 0.881, p<0.001) measurements. [10,11,[15][16][17][18] Upon the examination of radiological images of Chinese adults, Zeng et al found the mean MDA value to be 19.3 mm on the right and 19.4 mm on the left in male and 17.3 mm on the right and 17.4 mm on the left in female. [19] In a study conducted by Indurjeeth et al on the dry hip bones of the Black African population of South Africa, mean VDA, MDA, and LLAN values were found to be 54.84 mm, 31.30 mm, and 21.72 mm, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, a very strong positive statistically significant correlation was obtained between LH and IH (r: 0.853, p<0.001) and ADA and VDA (r: 0.881, p<0.001) measurements. [10,11,[15][16][17][18] Upon the examination of radiological images of Chinese adults, Zeng et al found the mean MDA value to be 19.3 mm on the right and 19.4 mm on the left in male and 17.3 mm on the right and 17.4 mm on the left in female. [19] In a study conducted by Indurjeeth et al on the dry hip bones of the Black African population of South Africa, mean VDA, MDA, and LLAN values were found to be 54.84 mm, 31.30 mm, and 21.72 mm, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Length of hip bone (LH) (7) The distance from the most superior point on the iliac crest to a plane drawn along the inferior surface of the ischium Width of hip bone (Ilium width) (WH) (7) The distance between the anterior superior iliac spine and the posterior superior iliac spine Minimum İliac Breadth (MIB) (8) The distance between the points where the arch of the greater sciatic notch meets the posterosuperior margin of the acetabulum and the anterior border of the ilium meets the anterosuperior margin of the acetabulum Iliac height (IH) (9) The distance between the central point of the acetabulum and the outermost point on the iliac crest Vertical diameter of acetabulum (VDA) (10) The longest diameter of acetabulum measured along the axis of the body of the ischium Anteroposterior diameter of acetabulum (ADA) (11l)…”
Section: Measurements Definitonmentioning
confidence: 99%
See 1 more Smart Citation
“…Acetabular measurements or dimension is crucial to diagnose various diseases that are related to the hip joint which also helps to check the recovery of patients and to access the stability of the hip joint (Sachdeva et al, 2019). These measurements of acetabulum are also helpful during surgical procedures for acetabular reconstruction using materials such as spikes and screws during fixation (Dhindsa, 2013).…”
Section: Introductionmentioning
confidence: 99%